Integration of Service Quality, Importance Performance Analysis, and Quality Function Deployment for Service Quality Analysis - Kharisma, Risky Ageng; Ambarwati, Rita; Hermawan, Sigit (Yayasan Riset dan Pengembangan Intelektual, 2024)
Companies that provide service offerings must prioritize service and customer comfort. Customers do not only assess the services provided; they also evaluate the comfort and performance of the employees serving them. Customer satisfaction is crucial since customers are the source of income and an excellent promotion medium. They share their experiences with others based on what they feel. Information technology services are currently in high demand, and with many competitors emerging, it is essential to build customer trust by fulfilling their needs to achieve customer satisfaction. This study aims to analyze the service quality at Dinotech Solution to determine how satisfied customers are with the services provided and to measure the quality of the services performed. Customers at the managerial level will be the subjects for data collection in this study. The data will be processed using Service Quality (Servqual) and Importance Performance Analysis (IPA), further clarified with the Quality Function Deployment (QFD) method in the house of quality. It is expected that this study will provide solutions to enhance customer satisfaction. The research results can also serve as actionable solutions for the company to attract more customers and retain existing ones.